THU0299 PATIENT GLOBAL ASSESSMENT OF DISEASE ACTIVITY IN BEHÇET'S SYNDROME: A MULTICENTER STUDY. (June 2019) - Floris, Alberto; Piga, Matteo; Espinosa, Gerard; Kougkas, Nikolaos; Monaco, Andrea Lo; Lopalco, Giuseppe; Orlando, Ida; Pirani, Vittorio; Santos, Ernestina; Pinto, Luísa Serpa; Bertsias, George; Cantarini, Luca; et al.
Abstract : Background: Disease activity evaluation is mandatory according to the OMERACT Core Set of Domains for Behçet's Syndrome (BS). Poor data are available on Patient (PtGA) and physician (PGA) global assessment of disease activity in BS. Objectives: To assess PtGA performance in patients with BS and how different disease manifestations influence the patient and physician's perception of disease activity. Methods: A multicenter cross-sectional cohort of consecutive BS patients was enrolled. Disease activity was evaluated by PtGA, PGA and the Behçet's disease current activity form (BDCAF). PtGA and PGA were assessed trough a single question ("How active was BS during the last week?") in a 10-cm visual analogic scale. Health related quality of life (HRQoL) perception was evaluated by the Physical Component Summary (PCS) and the Mental Component summary (MCS) of the SF36v2 questionnaire. Correlation between PtGA, PGA, BDCAF and between them and SF36v2 component summaries was assessed trough the Spearman's correlation coefficient (rho). Two separated multiple regression models were built to measure the independent effect (β regression) of each active clinical manifestation on PtGA and PGA. Results: Overall, 226 BS patients from 5 Mediterranean Countries were enrolled. Out of them, 111 (49.1%) were males and the median (IQR) age and disease duration were 46.9 (35.6-55.2) and 11.7 (5.9-20.8) years, respectively. The median (IQR) value of PtGA, PGA and BDCAF were 2.0 (0.3-5.0), 1.0 (0.0-3.0) and 3.0 (0.0-5.0), respectively. PtGA significantly correlated (Figure) with both PGA (rho 0.759. p < 0.001) and BDCAF (rho 0.523. p < 0.001), in support of its construct validity. PtGA scores were significantly higher than PGA with a mean (SD) difference of 0.8 (1.8), suggesting a different weighing of disease activity between patients and physicians. Indeed, PtGA and PGA were differently influenced by active clinical manifestations (Table). PtGA was mainly dependent on active mucocutaneous (β 0.243), gastrointestinal (β 0.216) and ocular (β 0.209) involvement whereas a major effect of ocular manifestations was observed in PGA (β 0.378). PtGA was correlated with worse HRQoL perception measured by PCS (rho -0.476. p > 0.001) and MCS (rho -451. p > 0.001). Conclusion: PtGA seems to be a valid outcome measure in BS and should be considered as a separate outcome measure or better be included in composite index for overall disease activity evaluation. Disclosure of Interests: Alberto Floris: None declared, Matteo Piga: None declared, Gerard Espinosa: None declared, Nikolaos Kougkas: None declared, Andrea Lo Monaco: None declared, Giuseppe Lopalco Speakers bureau: SOBI, BMS, Ida Orlando: None declared, Vittorio Pirani: None declared, Ernestina Santos: None declared, Luísa Serpa Pinto: None declared, George Bertsias: None declared, Luca Cantarini: None declared, Alberto Cauli: None declared, Ricard Cervera: None declared, João Correia: None declared, Marcello Govoni: None declared, Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Ana Martins da Silva: None declared, Piergiorgio Neri: None declared, Carlos Vasconcelos: None declared, Alessandro Mathieu: None declared